The Bishops and the Act of Exchange of 1559 - Heal, Felicity (The historical journal, 1974)
It is well known that the Tudor monarchs exerted highly effective control over the financial resources of the English Church, particularly in the years after the Henrician Reformation. So marked a feature of the sixteenth century were the demands which the Crown, followed by the rest of the leading laity, made upon the Church in order to gain easy profit, that the period has on occasions been characterized as the ‘ age of plunder ’ The dissolution of the monasteries, and its economic and social consequences, have long been the subject of scholarly attention and debate. The fortunes of the secular church, in contrast, have roused relatively little interest, except as a background to the Laudian revival. This is, of course, in part because the crisis which the parochial clergy, cathedral chapters and bishops, experienced, was less dramatic than that of the monks and chantry priests, and, perhaps partly because demands upon the secular church were often for taxation rather than for outright gifts of lands. None of the Tudors showed the slightest inclination to disturb the fundamental tithe relationship within the parishes, and there were very few, even among the most ardent advocates of reform, who spoke openly for the old Lollard concept of making tithe dependent upon the quality of the incumbent.